PENGARUH FAKTOR – FAKTOR MAKROEKONOMI TERHADAP JUMLAH PERUSAHAAN IPO (INITIAL PUBLIC OFFERING) DI INDONESIA PERIODE TAHUN 1995 – 2020 SERTA PERBANDINGAN PENGARUH PADA KONDISI SEBELUM DAN SESUDAH KRISIS 2008 - Jesrida Anlin; Harjum Muharam (Jurnal Akuntansi dan Pajak, 2023)
This research intends to examine the impact of macroeconomic factors on the number of companies which conduct initial public offerings (IPO) period 1995 – 2020, As well as comparing the impact of macroeconomic factors on the number of IPO before and after the 2008 Subprime Mortgage crisis to determine whether these conditions have a different impact. This research's sample consisted of 588 companies which held IPO period 1995 - 2020. This research technique includes multiple linear analysis techniques with hypothesis testing, specifically the t test and chow test. The result of this research show interest rates and stock market volatility have a negative and significant impact on the number of initial public offerings (IPO), while inflation and gross domestic product (GDP) have no significant impact on the number of initial public offerings (IPO). This research also shows that there is no difference between the effects of macroeconomic factors on the number of IPO before and after the 2008 Subprime Mortgage crisis.